Design Environmentally-Friendly Incinerator and Hybrid Smokeless Incinerator Sorong of Merchant Marine Polytechnic - Riyanto, Budi; Widarbowo, Dodik; Idris, Muh; Nugroho, Danang D.S.; Setiyono, Muji (Brilliance: Research of Artificial Intelligence, 2024)
The problem of waste is the subject of discussion from time to time, waste that is not managed properly has a negative impact on the environment. There needs to be a waste management system so that waste problems can be suppressed and overcome, the most effective method of overcoming waste is burning but the results of burning will cause pollution that can pollute the air and can affect the environment. In an effort to overcome the problem of environmentally friendly waste, the Sorong of Merchant Marine Polytechnic designed a waste handling system through the Design of Environmentally-Friendly and Hybrid smokeless incinerators whose work system uses smokeless combustion using “hybrid power” sources, solar cell and power plant company. This research uses qualitative methods referring to previous research. The Incinerator working system is to process waste in an environmentally friendly process using the automatic combustion method to turn waste into residue through several levels of filtering in the “incinerator chamber”. The combustion of waste will also cause smoke and gas which will be flowed by the "blower" then suppressed and eliminated using the "smoke and gas remover" system by isolating it in a room with a spray and sprinkle device that is driven by high-pressure water power from the "water pump". There are two filtration systems in this incinerator system, first "gas filtration" which is used to capture and trap harmful gases, second water filtration is used to filter waste water (aerosols) from the smoke and gas remover process, clean water filtering results will be accommodated and recirculated to the "smoke and gas remover" using a "water pump". The "Hybrid power" source in this tool is used to drive the "conveyor", "automatic waste door", "automatic lighter", "blower" and "water pump".